EXPERIMENTAL STUDY AND ANALYSIS OF WOUNDED TYPE D.C. MOTOR WITH VARIABLE POWER SUPPLY - Kumrey, G.R.; Mahobia, S.K. (International Journal of Engineering Technologies and Management Research, 2017)
In this paper we are observed about maximum R.P.M. , in this way we are used the Wounded type D.C. Motor with Variable Voltage Power Supply and 1Amp.,2Amp., 3Amp. For the purpose of the finding of the variable voltages we are used the voltages regulator. The Wounded type D.C. Motor are used in various industrial application.